Pengembangan Media Lectora Inspire dalam Pembelajaran Sains di Madrasah Ibtidaiyah - Prasetyo, Sigit (Jurnal Pendidikan Islam, 2015)
This is the Research and Development (R & D) on lectora inspire media development in science learning based on integration-interconnection with religion in MI. The result of this research development are (1) It has been developed lectora inspire product in material of living creature breeding, (2) the result of reviewer assessment, namely the category of Very Good (SB) with a score of 631 and a percentage of 86.85% and the assessment based on student responses have interval category between “Agree and Strongly Agree”, which resulted in a score of 635 with a percentage of 88.23%. in accordance with reviewers result limitation and the assessment in this study, the lectora inspire product is feasible and can be used as a learning media for science that based on integration-interconnection with religion in MI.